Soft‑chewable paracetamol tablets by Melt Granulation Method: formulation and characterization - Mohmad Sabere, Awis Sukarni; Mohd Suhaimi, Nur Anis Najlaa; Ahmed, Qamar Uddin; Mahat, Mohd Muzamir; Che Roslan, Nazreen; Azizi, Juzaili (Wolters Kluwer Health, 2021)
Oral drug delivery is the most preferred route for drug administration in the world, with tablets being one of the most common dosage forms. However, some people, particularly children and the elderly, have difficulty swallowing the tablets. Chewable tablets are the dosage form that can address the issue while also providing a valuable masking effect on drug taste, allowing patients to swallow the drugs more easily. Materials and Methods: In this study, the chewable tablets were manufactured using the melt granulation method, which resulted in tablets with a chewy texture. The tablets contained paracetamol as well as Arabic gum, starch, agar, and mannitol. Results: The drug release profiles for the fragmented form showed that 50% of the drug was released within 4 min and 100% was released within 30 min of the dissolution process. The intact form released nearly 90% of the drug within 2 h. Conclusion: Formulation 2 was determined as the best formulation. This tablets' formulation had passed all characterization tests and displayed a moderate hardness and chewy texture.